ChemInform Abstract: Experimental and Computational Evidence for KOt‐Bu‐Promoted Synthesis of Oxopyrazino[1, 2‐a]indoles. Issue 15 (24th March 2016) - Mahdavi, Mohammad; Hassanzadeh‐Soureshjan, Rasoul; Saeedi, Mina; Ariafard, Alireza; BabaAhmadi, Rasool; Ranjbar, Parviz Rashidi; Shafiee, Abbas
Abstract: Oxopyrazino[1, 2‐a]indole derivatives are prepared via a two‐step synthetic procedure including an Ugi‐four‐component reaction followed by transition metal‐free intramolecular hydroamination of the adducts.